2020
DOI: 10.3390/ijerph17186539
|View full text |Cite
|
Sign up to set email alerts
|

Communicating Evidence about the Causes of Obesity and Support for Obesity Policies: Two Population-Based Survey Experiments

Abstract: Public support for numerous obesity policies is low, which is one barrier to their implementation. One reason for this low support is the tendency to ascribe obesity to failings of willpower as opposed to the environment. Correlational evidence supports this position. However, the experimental evidence is mixed. In two experimental studies, participants were randomised to receive no message, messages about the environment’s influence on obesity (Study 1 & 2), or messages about the environment’s influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 59 publications
2
10
0
Order By: Relevance
“…Several studies have shown greater support for government policies is associated with an understanding that overweight is caused by the food environment and is outside the individual's control. 39,40 Reynolds et al (2020) has recently challenged these results, finding no change in support for policies when the environmental causes of obesity were communicated, 41 concluding in a metaanalysis that the different results could be due to insufficiently persuasive messages. 42 The 'nanny state' narrative by the food industry or in media may also be another contributor to how the public perceives regulatory measures.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown greater support for government policies is associated with an understanding that overweight is caused by the food environment and is outside the individual's control. 39,40 Reynolds et al (2020) has recently challenged these results, finding no change in support for policies when the environmental causes of obesity were communicated, 41 concluding in a metaanalysis that the different results could be due to insufficiently persuasive messages. 42 The 'nanny state' narrative by the food industry or in media may also be another contributor to how the public perceives regulatory measures.…”
Section: Discussionmentioning
confidence: 99%
“…Although the interventions mostly differed across studies, there are two principle reasons why intervention content is unlikely to fully account for these discrepant results. First, interventions sourced from these two studies were used in a third study that did not replicate the results (Reynolds, Vasiljevic, et al, 2020 ). Second, the intervention messages across all studies contained largely overlapping information.…”
Section: Discussionmentioning
confidence: 99%
“…While correlational evidence supports this approach, the experimental evidence provides mixed support. Several studies appear to suggest that communicating evidence of the environment’s influence on obesity has no effect on support for obesity policies (McGlynn & McGlone, 2018 ; Reynolds, Vasiljevic, et al, 2020 ; Young et al, 2016 ). Other studies report some statistically significant effects (Ortiz et al, 2016 ; Pearl & Lebowitz, 2014 ), but sometimes just in one subgroup (Garbarino et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations